Coronary arteries anomalies (CAA) as a cause of a sudden cardiac death (SCD) among young athletes - review - Opaliński, Hubert; Pietrzyk, Natalia; Obierzyński, Paweł; Kuroska, Gabriela; Piech, Piotr; Dryka, Joanna; Przybysławski, Kamil; Bieda, Szymon; Wokurka, Wojciech; Kozioł, Maciej; et al. (Journal of Education, Health and Sport, 2018)
Introduction and objective Congenital coronary arteries anomalies (CAA) are one of the most common causes of a sudden cardiac death (SCD) among young athletes. CAA are serious diagnostic and clinical issue because in many patients there are no characteristic clinical symptoms and commonly used tests are not enough to reveal many types of anatomical abnormalities. Authors of this review would like to present current state of knowledge of CAA and their diagnostics, as well as recommendations for proceeding in patients with diagnosed CAA to prevent SCD. Abbreviated description of the state of knowledge According to statistics CAA are rare congenital heart defects however they are associated with a more frequent occurrence of SCD. The mechanism of this phenomenon has not been fully explained but there are several hypotheses. The most important of which concerns the dimension of the angle of branch of the coronary artery from the sinus of Valsalva. Numerous clinical studies on SCD pay attention to the occurrence of asymptomatic CAA as the main cause of SCD right after hypertrophic cardiomyopathy. Among strategies of proceeding recommended after the diagnosis of CAA, there are pharmacological and surgical treatment, however it hasn’t been established which of them is the best for young athletes. Summary One of the most important things to prevent SCD in the course of CAA seems to be creating universal guidelines for early diagnosis and treatment of this congenital defect. Widespread learning first aid and increasing availability of automatic external defibrillators (AED) are also important. SCD of a young athlete is a tragedy not only for the family but also for the whole sporting environment, that is why it is in the public interest to find an answer to the question how we can prevent that cases in the future.